PERBANDINGAN SELF THERAPY PADA MAHASISWA PENDIDIKAN DOKTER DAN MAHASISWA PROFESI DOKTER TERHADAP KASUS TONSILOFARINGITIS - SALSABILA RAIHANANDA BAHTY (JURNAL ILMIAH SIMANTEK, 2021)
Self medication is an effort that is often done by someone to treat the symptoms of illness or disease that is being sufferedwithout first consulting a doctor. Self therapy (swamedication) becomes inappropriate if there is an error recognizing thesymptoms that arise, choosing a drug, dosage and delay in seeking advice / advice from health workers if complaintscontinue. Tonsillopharyngitis is inflammation of the tonsils and pharynx which has a predisposition to include chroniccigarette stimulation, certain foods, poor oral hygiene, patients who usually breathe through the mouth due to nasalcongestion, weather effects, and inadequate tonsillopharyngitis treatment. Handling this case is closely related to the use ofantibiotics. The use of antibiotics without rules can cause pathogenic bacterial resistance. To determine the profile of selftherapy in medical students (doctor education and doctor profession) in tonsillopharyngitis cases. Descriptive Observationalwith cross sectional approach involving 100 respondents preclinical students and 100 clinical students. This study usesprimary data using a validated questionnaire. There is a better self therapy behavior in clinical students as many as 80people (40%) than preclinical students as many as 62 people (31%). The statistical test results using the Chi Square Testobtained p value = 0.005 (p <0.05). It can be concluded that there is an effect of self therapy behavior between preclinicaland clinical students on tonsillopharyngitis cases.